HUBUNGAN DURASI DAN PERILAKU PENGGUNAAN LAPTOP TERHADAP NYERI PUNGGUNG BAWAH PADA MAHASISWA KEDOKTERAN UNIVERSITAS JAMBI - Tarawifa, Susan; Dalimunthe, Nurhanisah; Miftahurrahmah, Miftahurrahmah; Iskandar, MIrna Marhami; Quzwain, Fairuz (LPPM Universitas Jambi, 2022)
ABSTRACT Background: Low back pain or LBP is one of the most common health problems. One of the causes of LBP is behavior of the body in activities. this study aims to determined the correlation between duration and behavior of laptop usage on low back pain in medical students at Universitas Jambi Methods: This research is an analytical research. Sampling using purposive sampling in accordance with the inclusion criteria. The were analized by Spearman’s test. Results: Based on the characteristics, majority of respondents were female (75.8%) and had a BMI in the normal range (74.7%). Laptop were used the longest for a moderate amount of time (51,6%). Most of respondents use laptops with a bad posture (60,5%). The most common low back pain complaint was the waist (72.6%), followed by buttock (57.9%) and hip pain (54.2%). There is a relationship between the duration of laptop use and complaints of the waist pain (p value = 0.007), there is a relationship between the duration of laptop use and complaints of hip pain (p value = 0.011), and there is a relationship between the duration of laptop use and complaints of bottom pain (p value = 0.036 ). There is a relationship between the behavior of using a laptop with waist pain complaints (p value = 0.009), there is a relationship between the behavior of using a laptop with hip pain complaints (p value = 0.024), and there is a relationship between the behavior of using a laptop with bottom pain complaints (p value=0.004 ). Conclusion: There is a correlation between the duration of laptop use with low back pain. There is a correlation between the behavior of using a laptop with low back pain. Keywords: Low back pain, duration of laptop use,behavior of using a laptop. ABSTRAK Latar belakang: Nyeri punggung bawah atau NPB adalah salah satu masalah kesehatan yang sering terjadi. Salah satu penyebab NPB kesalahan perilaku tubuh dalam beraktivitas. penelitian ini bertujuan untuk mengetahui hubungan durasi dan perilaku penggunaan laptop terhadap nyeri punggung bawah pada mahasiswa Kedokteran Universitas Jambi. Metode: Penelitian ini merupakan penelitian analitik. Pengambilan sampel menggunakan purposive sampling yang sesuai dengan kriteria inklusi. Hasil dianalaisis dengan uji Spearman. Hasil: Berdasarkan karakteristik, responden terbanyak berjenis kelamin perempuan (75.8%) dan IMT kategori normal (74.7%). Durasi penggunaan laptop terbanyak yaitu durasi sedang (51.6%). Sebagian besar responden menggunakan laptop dengan postur tubuh buruk (60.5%). Keluhan nyeri punggung bawah yang paling banyak adalah nyeri pinggang (72.6%), kemudian nyeri pada bokong (57.9%), dan nyeri pinggul (54.2%). Terdapat hubungan antara durasi penggunaan laptop dengan keluhan sakit pinggang (p value=0.007), Terdapat hubungan antara durasi penggunaan laptop dengan keluhan sakit pinggul (p value=0.011), dan terdapat hubungan antara durasi penggunaan laptop dengan keluhan sakit bokong (p value=0.036). Adanya hubungan antara perilaku penggunaan laptop dengan keluhan sakit pinggang (p value=0.009), adanya hubungan antara perilaku penggunaan laptop dengan keluhan sakit pinggul (p value=0.024), dan adanya hubungan antara perilaku penggunaan laptop dengan keluhan sakit bokong (p value=0.004). Kesimpulan: Terdapat hubungan antara durasi penggunaan laptop terhadap nyeri punggung bawah. Terdapat hubungan antara perilaku penggunaan laptop terhadap nyeri punggung bawah. Kata kunci: Nyeri punggung bawah, durasi penggunaan laptop, perilaku penggunaan laptop.